Squid suckerin-spider silk fusion protein hydrogel for delivery of mesenchymal stem cell secretome to chronic wounds - Koh, Kenrick (2023)
Chronic wounds are non-healing wounds characterized by a prolonged inflammation phase. Excessive inflammation leads to elevated protease levels and consequently to a decrease in growth factors at wound sites. Stem cell secretome therapy has been identified as a treatment strategy to modulate the microenvironment of chronic wounds via supplementation with anti-inflammatory/growth factors. However, there is a need to develop better secretome delivery systems that are able to encapsulate the secretome without denaturation, in a sustained manner, and that are fully biocompatible. To address this gap, a recombinant squid suckerin-spider silk fusion protein is developed with cell-adhesion motifs capable of thermal gelation at physiological temperatures to form hydrogels for encapsulation and subsequent release of the stem cell secretome. Freeze-thaw treatment of the protein hydrogel results in a modified porous cryogel that maintains slow degradation and sustained secretome release. Chronic wounds of diabetic mice treated with the secretome-laden cryogel display increased wound closure, presence of endothelial cells, granulation wound tissue thickness, and reduced inflammation with no fibrotic scar formation. Overall, these in vivo indicators of wound healing demonstrate that the fusion protein hydrogel displays remarkable potential as a delivery system for secretome-assisted chronic wound healing.